Skeletal Aging and Osteoporosis Biomechanics and Mechanobiology - Silva, Matthew J.; Silva, Matthew J. (Studies in Mechanobiology, Tissue Engineering and Biomaterials, 2013)
The focus of this book is on mechanical aspects of skeletal fragility related to aging and osteoporosis. Topics include: Age-related changes in trabecular structure and strength; age-related changes in cortical material properties; age-related changes in whole-bone structure; predicting bone strength and fracture risk using image-based methods and finite element analysis; animal models of osteoporosis and aging; age-related changes in skeletal mechano responsiveness; exercise and physical interventions for osteoporosis.